2011
DOI: 10.1021/nn203260w
|View full text |Cite
|
Sign up to set email alerts
|

Complex Capacitance Scaling in Ionic Liquids-Filled Nanopores

Abstract: Recent experiments have shown that the capacitance of subnanometer pores increases anomalously as the pore width decreases, thereby opening a new avenue for developing supercapacitors with enhanced energy density. However, this behavior is still subject to some controversy since its physical origins are not well understood. Using atomistic simulations, we show that the capacitance of slit-shaped nanopores in contact with room-temperature ionic liquids exhibits a U-shaped scaling behavior in pores with widths f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
211
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(230 citation statements)
references
References 25 publications
18
211
1
Order By: Relevance
“…in pores below 1 nm (due to ions desolvation) is used as criteria for the improvement of the gravimetric capacitance [9][10][11][12][13][14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…in pores below 1 nm (due to ions desolvation) is used as criteria for the improvement of the gravimetric capacitance [9][10][11][12][13][14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…Although it was observed from experiments and some simulations that the best performances were obtained for CDCs with an average pore size matching the size of the ions [24][25][26][27][28] , in a recent theoretical study, Kondrat et al 29 have shown that the best average pore size depends on the operating voltage. Nevertheless their model was based on a description of the porous carbon based on a distribution of slit-like pores; the present results show that it would be necessary to inject a more detailed adsorption model to fully address this point.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was observed that the best performance of SCs can be realized when the average micropore size in nanostructured bulk electrodes (e.g., carbide-derived carbon) matches the size of the ions in the electrolyte [8][9][10][11][12][13][14][15] . It is expected that such a resonant effect is true even for defect-induced pores in quasi-two dimensional FLG substrates ( Figure 1a).…”
Section: Identification Of Best-suited Electrolytementioning
confidence: 99%